ANALISIS PENYEBAB INSIDEN PASIEN JATUH DI RAWAT INAP RS. Y DI KOTA PADANG - Dwi Novilolita; Yuniar Lestari; Hardisman Hardisman (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
Patient falls incident are unplanned incident with or without injuries in the inpatient unit. Based on minimum service standards, the fall incident which is part of patient safety is expected as 0%. Based on preliminary data from the Quality and Risk Management Committee in "Y" Hospital Padang there were 53 patient safety incidents where the most incidents were falls with 11 incidents. Inpatient is the most fallen location that is 5 incidents then followed by emergency room and outpatient. Therefore "Y" Hospital in Padang did not reach the standards of the Accreditation Commission that is zero accident. The purpose of this study was to analyze the causes and components that play a role in the incidence of falls in "Y" hospital in Padang. This study uses qualitative research by conducting semi-structured interviews, document review, and observation. Interviews were conducted with 21 informants. The components studied are individual characteristics (education, work experience, competence, age), nature of work (complexity of treatment, cooperation in units, disturbances/interruptions), physical environment (facilities), organizational and social environment (Standard Operating Procedure / SOP), and management factors (organizational structure, safety culture). The results showed that the minimum standard of education was sufficient but the percentage was not up to standard, the number of nurses needed was still lacking. The complexity of the treatment that consist of the type of diagnosis and the treatment has a high risk of falling, disruption in units is visiting hours that is not appropriate. Facilities that are still incomplete. The implementation of SOP is not optimal yet. The conclusion of the implementation of injury prevention due to falling patients is not optimal.